Coconut coir dust ratio affecting growth and flowering of potted petunia hybrids - Hongpakdee P. (2017)
© 2017, International Society for Horticultural Science. All rights reserved. Coconut coir dust is acceptable for the use as growing media, which promote flower quality and prolong shelf life in many ornamental plants. This research project was conducted to investigate the additional different portions of coconut coir dust (0, 25, 50 and 75%, v/v) in potting mixed media (40% rice husk, 20% rice husk charcoal, 20% sand and 20% fermented leaf compost by volume) on growth and flowering of ‘Coral Pink Wave’ petunia hybrids. The data for physiological parameters analyzed statistically showed significant effect of coconut coir dust amended treatment. Increase in the portion of coconut coir dust in substrate seems to decrease the number of branches, root dry weight, number of flowers, the percentage of flowering and flower dry weight when compared with non-coconut coir dust base. Negative correlation were observed between coconut coir dust portion and growth of petunia, i.e., number of branches (R=-0.94), stem and leaf dry weight (R=-0.87), roots dry weight (R=-0.95), number of flowers (R=-0.96), percentage of flowering (R=-0.81) and flower dry weight (R=-0.94). This finding might be associated with some physical properties of mixed media, which do not have good aeration and water fill pores. Thus, it is suggested that higher coconut coir dust ratio not quite be recommended as renewable potting mixed media for ‘Coral Pink Wave’ petunia hybrid growth.